Real-time interactive social environments: a review of BT's Generic Learning Platform - Michael Gardner; Holly Ward (Association for Learning Technology, 1999)
The vision of a single platform that supports all the key stakeholders within a wide range of distance learning activities has long been a dream of educationalists and commercial organizations alike. Such a platform could not only provide a consistent educational 'experience' for teachers and learners throughout their lives, but it could also provide administration and managerial support, all of which can be tailored to individual requirements.